2002
DOI: 10.1007/s004240100702
|View full text |Cite
|
Sign up to set email alerts
|

Protein variants of skeletal muscle regulatory myosin light chain isoforms: prevalence in mammals, generation and transitions during muscle remodelling

Abstract: The regulatory myosin light chains (rMLCs) of mammalian skeletal muscle display protein diversity arising from the existence of different isotypes and protein phosphorylation. Two-dimensional electrophoresis and immunoblotting allowed us to identify three variants of the slow and fast rMLC isoforms (designated LC2s, LC2s1, LC2s2, and LC2f, LC2f1, LC2f2, respectively, from less to more acidic). This study aimed to characterize their prevalence among different species and muscle types, the mechanism(s) of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 38 publications
9
27
0
Order By: Relevance
“…It is well established that the various light and heavy chains of myosin undergo a stepwise replacement from fast to slow isoforms during fibre type shifting [41,42], which has also been shown to occur in the case of regulatory elements of the contractile apparatus, such as the individual subunits of troponin [4]. The expanded views of 2-D landmark spots shown in Fig.…”
Section: Confirmation Of Fast-to-slow Muscle Transition By Contractilmentioning
confidence: 90%
See 1 more Smart Citation
“…It is well established that the various light and heavy chains of myosin undergo a stepwise replacement from fast to slow isoforms during fibre type shifting [41,42], which has also been shown to occur in the case of regulatory elements of the contractile apparatus, such as the individual subunits of troponin [4]. The expanded views of 2-D landmark spots shown in Fig.…”
Section: Confirmation Of Fast-to-slow Muscle Transition By Contractilmentioning
confidence: 90%
“…An elevation of aerobic-oxidative capacity, decreased fibre calibre and changes in the density of distinct muscle proteins, switches in isoform expression patterns and alterations in proteinprotein interactions are established biochemical and cell biological hallmarks of transformed skeletal muscles. This includes: (i) metabolic pathways such as the citric acid cycle, fatty acid oxidation and the respiratory chain which causes a drastic increase in enzymes of aerobic substrate oxidation [39,40], (ii) the contractile apparatus that undergoes a stepwise replacement of myosin light and heavy chains from fast isoforms to their slower counterparts [41,42], (iii) the ion-regulatory machinery of the excitation-contractionrelaxation cycle with a shift from fast to slower isoforms with respect to the SERCA-type Ca 21 -ATPases, the voltagesensing dihydropyridine receptor, the ryanodine receptor Ca 21 -release channel and various Ca 21 -binding proteins [43,44], (iv) the neuromuscular junction with distinct changes in the acetylcholinesterase and the nicotinic acetylcholine receptor [45,46] and, (v) a decrease in the supramolecular interaction pattern between Ca…”
Section: Introductionmentioning
confidence: 99%
“…The proteomic analysis of the age-related transformation of fibres agrees with findings from artificially induced fibre type transitions due to chronic low-frequency stimulation. Fast-to-slow transformation is associated with major alterations in the density and isoform expression pattern of both MHCs (Kirschbaum et al, 1989) and MLCs (Gonzalez et al, 2002). Changes in the expression levels and post-translational modifications of key contractile elements is a clear indication that senescent motor units undergo major physiological adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Differently expressed isoforms of proteins are the basis of muscle heterogeneity inherent to soleus and gastrocnemius muscles [10,15,[25][26][27]]. In the current study, this was shown by the variation in the relative abundances of MLC isoforms and metabolic enzymes as well as in the presence of parvalbumin in the white portion of gastrocnemius muscle [28].…”
Section: Discussionmentioning
confidence: 53%